Performance of Aroid under Jackfruit-Based Agroforestry System in Terrace Ecosystem of Bangladesh - Riyadh, ZA; Rahman, MA; Miah, MG; Saha, SR; Hoque, MA; Saha, S; Rahman, MM (Annals of Bangladesh Agriculture, 2019)
The terrace ecosystem is considered as hotspot of jackfruit tree (Artocarpus heterophyllus Lam) in Bangladesh having potential for understory cropping. However, most of the jackfruit orchards are often found utilized or underutilized. A field experiment was conducted under the jackfruit orchard to study the performance of aroids (Colocasia esculenta L.) from April to October, 2017 in Belabo upazila of Narsingdi district. Four distances (1, 2, 3 and 4 m) from the base of jackfruit tree were considered for aroid planting to evaluate its performance as agroforestry crop in comparison to sole aroid. Land use and economic performances of agroforestry and sole systems were also evaluated. The results indicated that the production of jackfruit increased by 62.73%, while the yield of aroid reduced by 33.48% in agroforestry systems as compared to the yields of sole (non-agroforestry) systems. In agroforestry system, the photosynthetically active radiation (PAR) was severely reduced by 85-77% on aroid crop that caused yield reduction. It was also observed that soil temperature was lower in agroforestry system as compared to sole cropping of aroid, while soil moisture showed inverse trend in sole jackfruit. Economic analysis in terms of benefit cost ratio (BCR) was 2.60 in agroforestry, while the BCR of sole aroid was only 1.83. The land equivalent ratio (LER) was 2.31 in agroforestry system. The present results indicate that aroid cultivation in jackfruit-based agroforestry system under terrace ecosystem can ensure overall higher production and improve economic return. Ann. Bangladesh Agric. (2019) 23(2) : 79-87